2013
DOI: 10.1111/acel.12039
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide linkage analysis for human longevity: Genetics of Healthy Aging Study

Abstract: Summary Clear evidence exists for heritability of human longevity, and much interest is focused on identifying genes associated with longer lives. To identify such longevity alleles, we performed the largest genome-wide linkage scan thus far reported. Linkage analyses included 2118 nonagenarian Caucasian sibling pairs that have been enrolled in fifteen study centers of eleven European countries as part of the Genetics of Healthy Ageing (GEHA) project. In the joint linkage analyses we observed four regions that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(112 citation statements)
references
References 41 publications
8
102
1
1
Order By: Relevance
“…Our findings indicated that cognitive and functional parameters (SMMSE, ADL scale and hand grip strength), self-reported health and clinical parameters (haemoglobin, creatinine and total cholesterol) are associated in 90+ sib-ships. This analysis suggests that the GEHA familial/genetics model of healthy aging allowed us to observe that the cognitive and physical abilities, together with the above mentioned haematochemical parameters appear to be influenced by familiarity/genetics, which has been recently demonstrated to play a role in the longevity of the sib-ships we analysed (Beekman et al 2013). Remarkably, also the self-reported health resulted to be associated in 90+ siblings, showing that well-being runs along families.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our findings indicated that cognitive and functional parameters (SMMSE, ADL scale and hand grip strength), self-reported health and clinical parameters (haemoglobin, creatinine and total cholesterol) are associated in 90+ sib-ships. This analysis suggests that the GEHA familial/genetics model of healthy aging allowed us to observe that the cognitive and physical abilities, together with the above mentioned haematochemical parameters appear to be influenced by familiarity/genetics, which has been recently demonstrated to play a role in the longevity of the sib-ships we analysed (Beekman et al 2013). Remarkably, also the self-reported health resulted to be associated in 90+ siblings, showing that well-being runs along families.…”
Section: Discussionsupporting
confidence: 60%
“…It can be considered the first of other similar investigations, on the assumption that analogous micro-heterogeneity is present in the 90+ populations recruited in the other geographic areas which contributed to the GEHA project. Indeed, the results of the genome-wide linkage analysis suggest that the Northern and Southern Europe populations contributed differently to the identification of the four chromosomal regions associated with longevity (Beekman et al 2013). Thus, the present study can help in interpreting the genetic results obtained by the GEHA project whose major aim is the comprehensive evaluation of phenotypic and genetic data.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 71%
“…Recent data also support an association of ApoE and mortality in long-lived individuals. A genome-wide linkage analysis with nonagenarians identified ApoE as a longevity gene (Beekman et al, 2013), which is in agreement with the results of a recent case-control genome-wide association study comparing long-lived individuals (mean age: 99.7 years) and Experimental Gerontology 53 (2014) [16][17][18][19][20][21][22][23] younger controls from Germany (Nebel et al, 2011). However, whether ApoE influences exceptional longevity (EL), i.e., reaching 100+ years of age, is more controversial.…”
Section: Introductionmentioning
confidence: 99%
“…A poly T repeat in an intronic polymorphism (rs10524523) (intron 6) in the TOMM40 gene, which encodes an outer mitochondrial membrane translocase involved in the transport of amyloid-β and other proteins into mitochondria, has been implicated in AD [31][32][33][34][35][36][37][38][39][40][41][42][43][44], and APOE-TOMM40 genotypes have been shown to modify disease risk and age at onset of symptoms [32][33][34][35][36][37]45], although the latter assumption needs replication due to contradictory results [36,[46][47][48][49]. A fixed-effect meta-analysis approach showed that rs4420638 at the TOMM40/APOE/APOC1 gene locus is associated with longevity [50,51]. Two independent associations with cognitive decline were found among European-Americans in the 19q13.32 region (rs769449, APOE intron; and rs115881343, TOMM40 intron); rs769449 was also associated with cognitive decline among African-Americans, but rs115881343 was not [52].…”
Section: Introductionmentioning
confidence: 99%